Amsterdam '60 - '80 : Twintig jaar beeldende kunst. - Belder, Lucky; Boers, Waling; Ellenbroek, Willem; Gribling, Frank; Hofland, H.J.A.; Ligthart, Pieter; Lubbers, Frank; Ruhé, Harry; Smithuijsen, Cas; van Grootheest, Tijmen (Amsterdam : Museum Fodor, 1982)
Abramovic, Marina & Ulay ; Andreas-Tüzüner, Isik ; Armando ; Asselbergs, Gustave ; van Bentum, Rik ; Berghuis, Jaap ; Beutener, Jan ; Blom, Ansuya ; Boezem, Marinus ; Boissevain, Guus ; Brouwn, Stanley ; Buisman, Sjoerd ; Carrión, Ulises ; Cassée, Dick ; Constant ; Content, Eli ; Couzijn, Wessel ; Cremer, Jan ; Daniels, René ; Dekkers, Ad ; Dibbets, Jan ; Diederen, Jef ; Dukkers, Eduard ; Dumas, Marlene ; van Elk, Ger ; Engels, Pieter ; Flögel, Guus ; Freymuth, Alphons ; Fridfinnsson, Hreinn ; Gachnang, Johannes ; de Goede, Kees ; Graevenitz, Gerhard von ; Gribling, Frank ; Grootveld, Robert Jasper ; Gudmundsson, Sigurdur ; Haak, Wim ; De Haan, Wim ; Henneman, Jeroen ; Heyboer, Anton ; Holstein, Pieter ; Hoover, Nan ; Jaring, Cor ; van Keulen, Floor ; Kley, Theo ; Koetsier, Hans ; van Koningsbruggen, Rob ; Lataster, Ger ; Lucassen ; Melle ; Niermeijer, Theo ; Nijssen, René ; Raetz, Markus ; Reneman, Max ; Roeland, Jan ; Rogge, Cornelius ; Schippers, Wim T. ; Sierhuis, Jan ; Smit, Robert ; Smits, Kees ; Struycken, Peter ; Tajiri, Shinkichi ; Ulay ; Visser, Carel ; Volten, André ; Vroegindeweij, Leo ; Wagemaker, Jaap ; Weiner, Lawrence ; Zuyderland, Siet
geboortedata per kunstenaar
Amsterdam '60 - '80 : twintig jaar beeldende kunst / twenty years of fine arts, Museum Fodor Amsterdam, 09.04 - 11.07.1982
Nederlands & Engels
boek
Keywords: Amsterdam